THE PROBLEM OF CONTINUITY OF TRAINING OF FUTURE EDUCATORS AND TEACHERS OF ELEMENTARY SCHOOL ON ORGANIZATION OF ARTISTIC AND AESTHETIC ACTIVITY OF CHILDREN - Наталія Колесник (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article reveals peculiarities in realization of the continuity principle in training future educators and teachers of elementary school on organization of children's artistic and aesthetic activity. The indexes of child's readiness for school in different spheres of its activity, and in particular, in artistic and aesthetic one have been determined in this research. Description of depicting activity of children of preschool age has been made, and the types of unconventional technologies of implementation of artistic images have been presented. There have also been determined the following directions in training of future educators and teachers of elementary school on organization of artistic and aesthetic activity of children: theoretical, organizational and methodical, and practical. Basic concepts, such as "continuity of education", "continuity", "artistic and aesthetic activity" have been analyzed in this paper. A role and value of creative imagination and thinking of children have been revealed in the context of artistic and aesthetic activity. Experience in training of future educators and teachers of primary school on organization of artistic and aesthetic activity of children has been reflected. The article also presents regularities in development of a creative personality of preschool and junior school age.